Insulin resistance and adverse lipid profile in untreated very early rheumatoid arthritis patients: A single-center, cross-sectional study in China - Lu Ye; Xin Zhang; Huaxiang Wu; Yahui Chen; Haibo Zhou; Qiaohong Wang; Weihong Xu (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate the presence and factors related to insulin resistance (IR) in untreated very early rheumatoid arthritis (RA) patients. Patients and methods: Between June 2020 and July 2021, a total of 90 RA patients (29 males, 61 females; mean age: 49.3±10.2 years; range 24 to 68 years) and 90 age-, sex- and body mass index (BMI)-matched controls (35 males, 55 females; mean age: 48.3±5.1 years; range 38 to 62 years) were included. Homeostatic model assessment was applied to evaluate IR (HOMA-IR) and β-cell function (HOMA-β). Disease activity score 28 (DAS28) was used to estimate disease activity. Lipid profile, hemoglobin A1c (HbA1c), glucose, insulin, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) were measured. Logistic regression analysis was performed to investigate the relationship between the IR and clinical features of RA patients. Results: The RA patients had higher HOMA-IR values (p<0.001) and adverse lipid profile. The IR was positively correlated with age (r=0.35, p<0.01), CRP (r=0.42, p<0.001), ESR (r=0.33, p<0.01), disease duration (r=0.28, p<0.01), and DAS28 (r=0.50, p<0.001). The DAS28, CRP and age, but not sex and menopausal status, were independently associated with IR. Conclusion: Insulin resistance was present in untreated very early RA patients. The DAS28, CRP, and age were independent predictors for the presence of IR. Based on these findings, RA patients should be evaluated early for the presence of IR to reduce the risk of metabolic diseases.